Impact of amendments on the physical properties of soil under tropical long-term no till conditions - Filho, Antonio C.A. Carmeis [UNESP]; Crusciol, Carlos A.C. [UNESP]; Guimarães, Tiara M. [UNESP]; Calonego, Juliano C. [UNESP]; Mooney, Sacha J. (Public Library of Science (PLoS), 2016)
Tropical regions have been considered the world's primary agricultural frontier; however, some physico-chemical deficiencies, such as low soil organic matter content, poor soil structure, high erodibility, soil acidity, and aluminum toxicity, have affected their productive capacity. Lime and gypsum are commonly used to improve soil chemical fertility, but no information exists about the long-term effects of these products on the physical attributes and C protection mechanisms of highly weathered Oxisols. A field trial was conducted in a sandy clay loam (kaolinitic, thermic Typic Haplorthox) under a no-tillage system for 12 years. The trial consisted of four treatments: a control with no soil amendment application, the application of 2.1 Mg ha-1 phosphogypsum, the application of 2.0 Mg ha-1 lime, and the application of lime + phosphogypsum (2.0 + 2.1 Mg ha-1, respectively). Since the experiment was established in 2002, the rates have been applied three times (2002, 2004, and 2010). Surface liming effectively increased water-stable aggregates > 2.0 mm at a depth of up to 0.2 m; however, the association with phosphogypsum was considered a good strategy to improve the macroaggregate stability in subsoil layers (0.20 to 0.40 m). Consequently, both soil amendments applied together increased the mean weight diameter (MWD) and geometric mean diameter (GMD) in all soil layers, with increases of up to 118 and 89%, respectively, according to the soil layer. The formation and stabilization of larger aggregates contributed to a higher accumulation of total organic carbon (TOC) on these structures. In addition to TOC, the MWD and aggregate stability index were positively correlated with Ca2+ and Mg2+ levels and base saturation. Consequently, the increase observed in the aggregate size class resulted in a better organization of soil particles, increasing the macro-porosity and reducing the soil bulk density and penetration resistance. Therefore, adequate soil chemical management plays a fundamental role in improving the soil's physical attributes in tropical areas under conservative management and highly affected by compaction caused by intensive farming.